OPTIMALISASI PERAN BUMDES MELALUI PEMBENTUKAN PASAR SENJA UMKM DALAM RANGKA MENINGKATKAN PENDAPATAN ASLI DESA (PAD) - Fikri, Aula Ahmad Hafid Saiful; Afandi, Muhammad Roestam; Riani, Lilia Pasca; Kusumawardani, Nita (Jurnal Pengabdian Masyarakat AbdiMas, 2024)
This Community Service (PkM) activity aims to develop the concept of the twilight market in optimizing the role of BUMDes in increasing the Original Income of Gemblegan Village, Kalikotes District, Klaten Regency by providing assistance in developing and improving the management of the twilight market as one of the business units owned by BUMDes Makmur. .The target audience of this PkM is as many as 20 MSMEs with various business fields ranging from snacks, handicrafts to the business of catering services and management training to the managers of the Twilight Market.The method or approach that will be carried out is by means of lectures, discussions, direct training, business management assistance and additional capital in the form of production equipment and packaging to MSME partners. As for the manager of the twilight market, assistance is provided in the event organizer and Fundrising and SponsorshipIndicators of the success of the activity can be seen from the 11 evaluation indicators carried out by the service team in the form of filling out questionnaires by the participants. The indicators are the suitability of the activity with the objectives, the suitability of the material to the needs of the participants, the quality of the material provided, the mastery of the material by the resource person, the delivery of the material by the resource person, the systematic flow of material delivery, the participation of the resource person to the participant, the proximity of the resource person to the participant, the services provided by the service team, follow-up of problems by resource persons, and willingness of participants to take part in activities if held again.